Breeze Potential Along the Brazilian Northern and Northeastern Coast - Souza,Dayana Castilho de (2017)
ABSTRACT The breeze potential along the Brazilian northern and northeastern coast was studied using wind data from the Climate Forecast System Reanalysis for the period between 1980 and 2010. March and September were considered, which are representative of the rainy and dry (or less rainy) periods, respectively. The Brazilian northern and northeastern coast is composed by meridionally oriented coastlines (Amapá State coast and eastern coast of Northeast Brazil) and a zonally oriented coastline (Brazilian northern coast east of Marajó Island). Along the meridionally oriented coastlines, the breeze potential was mainly related to the zonal wind and extended inland over 1 - 2° from the shore. The daily zonal wind cycle maximum (minimum), which represents the land (sea) breeze potential, occurred at ~0700 UTC (~1900 UTC). Along the zonally oriented coastline, the breeze potential was mainly related to the meridional wind and extended inland and offshore over 2 - 3° from the shore. At the shore, the daily meridional wind cycle maximum (minimum), which represents the land (sea) breeze potential, occurred at ~1000 UTC (~2200 UTC). Phase propagation occurred from the shore inland in March and September and also offshore in September. In general, for the entire Brazilian northern and northeastern coast, the breeze potential frequency was higher in September (20 - 25 days per month). In March, while the frequency slightly decreased over the meridionally oriented coastlines (to 15 - 20 days per month), the frequency sharply decreased over the zonally oriented coastlines to 5 - 10 days per month in landside coastal areas and vanished in seaside coastal areas. Higher frequency was generally related to lower interannual variability, and there was significant correlation between the interannual variability of the frequency and oceanic indices, along specific coastal areas. The features of the breeze potential areas obtained in this study complement the results from others and provide a more complete depiction of breeze features along the entire Brazilian northern and northeastern coast.